Colors in descriptive art - Sattorova Sarvinoz Ortiqboy qizi; Abdullayev Alimardon Khaydarovich; Sodikova Irodahon Gayratjon qizi (Research Parks Publishers, 2020)
The article is intended for those who work and study in the field of fine and applied arts, to determine the basic characteristics of achromatic and chromatic colors, the study of additive and subtractive synthesis methods, spectral characteristics, color whiteness and color instability.